Do scaffolding interactions exist in the Thai classroom? - Patcharee - Scheb-Buenner, (Penerbit UKM, 2013)
This study reports on how five Thai teachers in a private university scaffold their students in an EFL classroom. The context of this study is teacher-fronted instruction and low proficiency students. A case study using an observation method is employed. The study reveals basic types of instructional activities: focus on form and focus on meaning. Scaffolding is explored using frameworks adopted from Wood, Bruner and Ross (1976) and van Lier (1996). The findings illustrate that the verbal interaction of Thai teachers with their students reflects scaffolding features described by Wood, Bruner and Ross (1976) while slightly reflecting van Lier’s description. The study summarizes the features of scaffolding in the teacher-fronted instruction. This embraces all the findings in relation to form and meaning-focused activities. Scaffolding in the form-focused activities displays long sequentiality, less contingency, and less contextual support, while scaffolding in the meaning-focused activities consists of short sequentiality, more contingency, and contextual support. The study offers the EFL teachers teaching in a university level and dealing with low proficiency learners and teacher-fronted instruction an approach to teach and earn their learners’ engagement. The teachers who employ scaffolding should be aware of the usefulness of it by combining the strengths of form-focused and meaning-focused activities. Scaffolding attributes should be gradually provided in order that low proficiency students can engage in interaction with the teachers. Most importantly, the teachers who adopt scaffolding in their teaching should be aware of the concepts of both frameworks which will make scaffolding a practical and effective approach.